Nitrogen optimization coupled with alternate wetting and drying practice enhances rhizospheric nitrifier and denitrifier abundance and rice productivity - Abid, Abbas Ali; Zhang, Qichun; Adil, Muhammad Faheem; Batool, Itrat; Abbas, Muhammad; Hassan, Zeshan; Khan, Azhar Abbas; Castellano-Hinojosa, Antonio; Zaidi, Syed Hassan Raza; Di, Hongjie; Abdeslsalam, Nader R. (Frontiers in Plant Science, 2022)
Optimizing nitrogen (N) fertilization without sacrificing grain yield is a major concern of rice production system because most of the applied N has been depleted from the soil and creating environmental consequences. Hence, limited information is available about nutrient management (NM) performance at specific site under alternate wetting and drying (AWD) irrigation compared to conventional permanent flooding (PF). We aimed to inquire about the performance of NM practices compared to the farmer’s fertilizer practice (FFP) under PF and AWD on rhizospheric nitrifier and denitrifier abundance, rice yield, plant growth, and photosynthetic parameters. Two improved NM practices; nutrient management by pig manure (NMPM); 40% chemical N replaced by pig manure (organic N), and nutrient management by organic slow release fertilizer (NMSR); 40% chemical N replaced by organic slow-release N were compared. The results showed an increased total grain yield (16.06%) during AWD compared to PF. Compared to conventional FFP, NMPM and NMSR significantly increased the yields by 53.84% and 29.67%, respectively, during AWD. Meanwhile, PF prompted a yield increase of 45.07% and 28.75% for NMPM and NMSR, respectively (p <0.05) compared to FFP. Besides, a significant correlation was observed between grain yield and nitrogen content during AWD (R2 = 0.58, p <0.01) but no significant correlation was observed during PF. The NMPM contributed to photosynthetic attributes and the relative chlorophyll content under both watering events. Moreover, relatively higher abundances of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) were observed during AWD and the highest value was found after the late panicle stage. Our results suggest that the AWD-NMPM model is the best option to stimulate nitrifier and denitrifier genes abundance and promote rice production.